Optic Disc Melanocytoma: Case Report - Köhle, Ülkü; Çelebi, Serdal; Yılmaz, Turgut; Aydemir, Orhan; Kükner, Şahap (Fırat University, 2003)
A pigmented optic nerve head lesion was detected on fundoscopy in a 57 years old female who presented with bad distance visual acuity. Based on clinical findings and ancillary studies, our diagnosis was (presumed) optic disc melanocytoma, and periodic examinations were scheduled. One year later the tumour size did not show any change. Patients with melanocytoma should be examined at regular intervals, serial fundus photographs are useful for monitoring growth and suspecting malignant transformation.

Uzağı net görememe yakınması ile başvuran 57 yaşındaki kadın hastada optik sinir başında pigmente bir lezyon saptandı. Klinik bulgular ve tanıya yardımcı testler ile hastaya olası optik disk melanositomu ön tanısı kondu, periyodik kontrol muayeneleri planlandı. Bir yıllık izlem sonunda tümör büyüklüğünde değişiklik olmadı. Melanositoma tanısı düşünülen hastalar düzenli aralıklar ile takip edilmelidir. Periyodik izlem ve fundus fotoğrafları lezyon büyümesinin takibinde ve malign dönüşüm olasılığının belirlenmesinde önemlidir.
Optik Disk Melanositomu: Olgu Sunumu